Paradigm of Law and Human Rights as a Protection of Academic Freedom in Indonesia - Wicaksana Prakasa, Satria Unggul (Human Rights in the Global South (HRGS), 2023)
Various attacks on academic freedom in Indonesia are like an iceberg phenomenon. The conditions are very worrying but not surprising, considering that repressive practices in the academic world are common in Indonesia. How is the legal mechanism of human rights and theoretical views responding to the threats to academic freedom in Indonesia. This research uses socio-legal study methods to regarding academic freedom in Indonesia and the patterns that follow. The purpose of this research is to rehabilitate and recover victims of terror and threats to academic freedom and ensure that similar cases are not repeated. Various models of threats and attacks on academic freedom, such as: the use of the judiciary to repress academics, banning and followed by sweeping of left books, prohibition or sanctions on teaching methods, forced dissolution of scientific discussions/forums both by campuses and by law enforcement officials and even groups of thugs, Stigmatization which was followed by violence against lecturers and students, as well as threats of violence and terror and even followed by attempts of persecution became a very worrying problem in the situation of academic freedom in Indonesia. Equally important, there is a need for a human rights legal system related to academic freedom that is institutionalized, strong, and binding so that it becomes a code of conduct for exercising academic freedom in Indonesia.